Thermal comfort in healthcare waste management buildings: insights from Seti Hospital, Dhangadhi, Nepal - Rana, Vishesh; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2024)
Thermal comfort in waste management studies is emerging as a growing concern, particularly in ensuring sustainable goals align with the well-being of workers. Under the scorching summer temperatures of up to 42.2°C, waste management workers at Seti Provincial Hospital, Dhangadhi, Nepal, experience significant thermal discomfort while handling infectious waste. Recognizing this challenge, this study investigates the thermal comfort of waste management workers at Seti Provincial Hospital, Dhangadhi, Nepal, and the impact of an internally heat-generating autoclave machine on the building’s material and thermal performance. Despite extensive literature on waste management principles and the functional design of healthcare waste management blocks, there is a noticeable gap regarding thermal comfort in such facilities. This research aims to fill that gap by focusing on healthcare waste management buildings in subtropical climatic conditions in Nepal. The research uses both quantitative and qualitative methods. Indoor temperatures in the treatment zone and office space were measured and compared with outdoor temperatures over a seven-day period. Moreover, a twice-daily questionnaire survey over a week assessed workers’ thermal sensations and preferences. Surface temperatures inside and outside the treatment zone were recorded to analyze the building envelope’s response to the autoclave’s heat generation. Findings indicate that workers experience extreme thermal discomfort during summer, highlighting the necessity for strategic autoclave placement to optimize thermal comfort and the adoption of passive design strategies during the design phase.